Phase 2B randomized controlled trial of NP001 in amyotrophic lateral sclerosis: Pre‐specified and post hoc analyses. Issue 1 (3rd June 2022) - Miller, Robert G.; Zhang, Rongzhen; Bracci, Paige M.; Azhir, Ari; Barohn, Richard; Bedlack, Richard; Benatar, Michael; Berry, James D.; Cudkowicz, Merit; Kasarskis, Edward J.; Mitsumoto, Hiroshi; Manousakis, Georgios; et al.
Abstract: Introduction/Aims: ALS is a heterogeneous disease that may be complicated or in part driven by inflammation. NP001, a regulator of macrophage activation, was associated with slowing disease progression in those with higher levels of the plasma inflammatory marker C‐reactive protein (CRP) in phase 2A studies in ALS. Here, we evaluate the effects of NP001 in a phase 2B trial, and perform a post hoc analysis with combined data from the preceding phase 2A trial. Methods: The phase 2B trial enrolled 138 participants within 3 y of symptom onset and with plasma hs‐CRP values >1.13 mg/L. They were randomized 1:1 to receive either placebo or NP001 for 6 mo. Change from baseline ALSFRS‐R scores was the primary efficacy endpoint. Secondary endpoints included vital capacity (VC) change from baseline and percentage of participants showing no decline of ALSFRS‐R score over 6 mo (non‐progressor). Results: The phase 2B study did not show significant differences between placebo and active treatment with respect to change in ALSFRS‐R scores, or VC. The drug was safe and well tolerated. A post hoc analysis identified a 40‐ to 65‐y‐old subset in which NP001‐treated patients demonstrated slower declines in ALSFRS‐R score by 36% and VC loss by 51% compared with placebo. A greater number of non‐progressors were NP001‐treated compared with placebo ( p  = .004). Discussion: Although the phase 2B trial failed to meet its primary endpoints, post hoc analyses identified a subgroup whose decline in ALSFRS‐R and VC scores were significantly slower than placebo. Further studies will be required to validate these findings.